Factors Associated with Diarrhea among Children Under Five Years of Age in Banten Province, Indonesia - Rohmawati, Nida; Panza, Alessio; Lertmaharit, Somrat (Journal of Health Research, 2017)
The data from Indonesian National Socio-economic Survey 2007 and Basic Health Research 2007 was used to examine the factors associated with diarrhea among children under-five years of age in Banten Province, Indonesia. A two stage sampling was done using probability proportional to the household’s number. Data analysis was done using Pearson’s Chi-square test and binary logistic regression. The prevalence of diarrhea among under-five old children was found to be 18.9%. The highest risk was in age group 6-11 months, low education mother (p-value = 0.001) and without gender influences. Mother’s defecation place (p-value < 0.001) and hand washing behavior (p-value <0.001) were found to be significant. Teenage mothers were found to have high risk of having children with diarrhea (p-value =0.042) and the highest percentage of never practiced hand washing with soap (15.8%). Unsafe drinking water source and poor physical quality of drinking water were associated with diarrhea in children (p-value <0.001 and 0.005) as well as the household which shared drinking water source and latrine, used open water container, open liquid drainage channel, and did not use septic tank for feces landfills. Exclusive breast feeding, good nutrition, vitamin A supplementation, measles immunization were not enough to prevent under-five old children from diarrhea. Health education, postpone young marriage, use of safe drinking water source and latrine, are recommended. Longitudinal study is needed to identify confounding factors, causal relationships and seasonal differences in the epidemiology of diarrhea.